Evaluation of in vivo Antidiabetic, Antidyslipidemic and in vitro Anti-Oxidant Activity of Extract and Solvent Fractions of Discopodium penninervum Hoschst Leaf in Mice: Normoglycemic and Streptozocin-Induced Model - Jifar WW; Debele GR; Kanfe SG; Mule CT (Dove Medical Press, 2022)
Wakuma Wakene Jifar,1 Gebiso Roba Debele,2 Shuma Gosha Kanfe,3 Chaltu Takele Mule4 1Department of Pharmacy, College of Health Sciences, Mattu University, Mettu, Oromia, Ethiopia; 2Department of Public Health, College of Health Sciences, Mattu University, Mettu, Oromia, Ethiopia; 3Department of Health Informative, College of Health sciences, Mattu University, Mettu, Oromia, Ethiopia; 4Department of Midwifery, School of Nursing and Midwifery, Debre Berhan University, Debre Berhan, EthiopiaCorrespondence: Wakuma Wakene Jifar, Tel +251 963421238, Email wakewakish05@gmail.comBackground: Diabetes mellitus has become a huge global public health and economic issue. The shortcomings of current medicines, as well as their serious side effects, prompted a focused quest for natural medicinal agents. In Ethiopia, the leaf of Discopodium penninervum Hoschst has been utilized in the traditional health system to treat diabetes. The goal of this study was to confirm the anti-diabetic, anti-dyslipidemia, and anti-oxidant activity of Discopodium penninervum Hoschst leaf in both in vitro and in vivo.Methods: In the normoglycemic, glucose-loaded, and streptozotocin-induced diabetic mouse models, the blood glucose-lowering effects of extract and solvent fractions of the leaf of Discopodium penninervum Hoschst were tested. The weight and lipid profile of streptozotocin-induced diabetic mice were assessed after treatment with leaf extract and solvent fractions for 14 days. The DPPH test was used to assess the antioxidant activity of the plant leaf extract.Results: In the normoglycemic model and glucose loaded test, the leaf extract of Discopodium penninervum Hoschst demonstrated significant blood glucose decrease (34.1%, p< 0.001) and 44.5%, p< 0.001, respectively, when compared to the normal control. When compared to a diabetic control group, extract and solvent fractions significantly (p< 0.001) reduced blood glucose levels on the 14th day in the streptozotocin-induced diabetic model. In addition, serum TC, STG, TG, LDL, and VLDL levels were reduced significantly (p< 0.001). IC50 values of leaf extract and a standard medication (ascorbic acid) in the antioxidant activity test were 4.1g/mL and 10.23g/mL, respectively.Conclusion: The hydro-alcoholic leaf extract and solvent fractions of Discopodium penninervum Hoschst leaves have demonstrated blood glucose-lowering effect, which justify ethnobotanical use, and can therefore be used as a good insight for new anti-diabetic medication source with a call for additional studies.Keywords: diabetic mellitus, Discopodium penninervum Hoschst, streptozotocin, blood glucose level